Intravascular ultrasound guided transcatheter electrosurgical revascularization of an interrupted aortic arch. Issue 1 (July 2022) - Visveswaran, Gautam K.; Vijaykumar, Snehitha; Michael, Mark; Cohen, Marc; Verma, Rajiv
Abstract: Interrupted aortic arch is a rare (prevalence 1:100000) but malignant cause of secondary hypertension, with late sequela of early myocardial infarction, stroke, and heart failure. We present the case of a 49-year-old male patient with aortic interruption successfully treated by intravascular ultrasound guided transcatheter electrosurgical wire crossing and revascularization using a covered stent. Learning objective: Transcatheter electrosurgical wire techniques utilizing intravascular ultrasound facilitate safe and effective percutaneous revascularization of complex aortic coarctation patients.